The synthesis of SiO2@CdS nanocomposites using single-molecule precursors - Monteiro, Olinda C. (2012)
A chemical method for preparing cadmium sulfide nanocrystals over silica surfaces is reported. This is a one-step synthetic method involving the chemical degradation of alkyldithiocarbamato complexes of cadmium in the presence of submicrometric SiO2 particles. The X-ray powder diffraction patterns of the SiO2@CdS nanocomposites show diffraction peaks consistent with the presence of hexagonal CdS. Visible spectroscopy and scanning and transmission electron microscopy indicate that an inorganic composite formed by islands of CdS nanocrystals at the SiO2 surfaces. The SiO2@CdS nanocomposites can, in turn, be capped with a protective layer of SiO2 using the Sto¨ber method.